Development of mechanical tube feeding method for construction of continuously reinforced concrete pavement (CRCP). Issue Volume 21:Issued 7(2020) (6th June 2020) - Choi, Pangil; Won, Hoonill; Cho, Yoon-Ho; Won, Moon
ABSTRACT: In South Korea, the performance of continuously reinforced concrete pavement (CRCP) has been better than that of jointed concrete pavement (JCP). However, most of the Portland cement concrete (PCC) pavements in South Korea have been JCP, primarily due to the difficulty in providing extra space along the edge of the pavement needed for concrete delivery in CRCP construction. In a tube-feeding method (TFM), concrete can be supplied from the front of a paver, which could facilitate CRCP construction without extra space needed. In the present study, efforts were made to improve the capability of TFM in placing longitudinal steel at correct elevations, which resulted in the development of tube feeding equipment (TFE). Field testing results showed that the key to ensuring steel placement at correct elevations was to keep longitudinal steel in adequate tension. The distance from the back of the tubes and the front of the mould, up to 1500 mm, did not have substantial effects on the steel settlement. To evaluate the viability of CRCP construction with TFE, a 400 m long CRCP section with 300 mm slab thickness and 8.2-m width was constructed and performance monitored.